Application of a Low Cost Ceramic Filter for Recycling Sand Filter Backwash Water - Md Shafiquzzaman (Water, 2018)
The aim of this study is to examine the application of a low cost ceramic filter for the treatment of sand filter backwash water (SFBW). The treatment process is comprised of pre-coagulation of SFBW with aluminum sulfate (Alum) followed by continuous filtration usinga low cost ceramic filter at different trans-membrane pressures (TMPs). Jar test results showed that 20 mg/L of alum is the optimum dose for maximum removal of turbidity, Fe, and Mn from SFBW. The filter can be operated at a TMP between 0.6 and 3 kPa as well as a corresponding flux of 480–2000 L/m2/d without any flux declination. Significant removal, up to 99%, was observed forturbidity, iron (Fe), and manganese (Mn). The flux started to decline at 4.5 kPa TMP (corresponding flux 3280 L/m2/d), thus indicated fouling of the filter. The complete pore blocking model was found as the most appropriate model to explain the insight mechanism of flux decline. The optimum operating pressure and the permeate flux were found to be 3 kPa and 2000 L/m2/d, respectively. Treated SFBW by a low cost ceramic filter was found to be suitable to recycle back to the water treatment plant. The ceramic filtration process would be a low cost and efficient option to recycle the SFBW.